Management of Innovations and Innovative Process: Concept, Essence, Classification and Diffusion - Gureva, Maria A.; Kirillov, Andrey V.; Vinichenko, Mikhail V.; Melnichuk, Aleksandr V.; Melnychuk, Yulyia A. (International Review of Management and Marketing, 2016)
The development, introduction of new products are important for companies as means of improving the competitiveness and the elimination of the company depending on the discrepancy between the life cycles of products. In modern conditions, the product update is a rapid pace. The system of innovative management is necessary for successful implementation of professional innovations introduction at the enterprise. Innovative management is one of the directions of the strategic management performed on the top-level management of the company. Its purpose is to determine the main directions of scientific-technical and production activities of the company in the following areas: gap-elaboration and introduction of new products (innovation); modernization and improvement of products; further development of the production of traditional products; removal from production of outdated production. Innovations are peculiar both dynamic, and static aspects. In the latter case the innovation is represented as the result of the research and production cycle (RPC), these results have an independent set of problems. Innovative process is connected with creation, development and distribution of innovations. It follows from the foregoing that the innovation result needs to be considered taking into account innovative process. For innovation are equally important, all three properties: the scientific and technological innovation, industrial applicability, tradability. Keywords: management, management of innovations, innovative process, concept, innovation JEL Classifications: O31, O32, O39